Circulating microRNAs as predictive biomarkers of myocardial infarction: Evidence from the HUNT study. (October 2019) - Velle-Forbord, Torbjørn; Eidlaug, Maria; Debik, Julia; Sæther, Julie Caroline; Follestad, Turid; Nauman, Javaid; Gigante, Bruna; Røsjø, Helge; Omland, Torbjørn; Langaas, Mette; Bye, Anja
Abstract: Background and aims: Several risk prediction models for coronary heart disease (CHD) are available today, however, they only explain a modest proportion of the incidence. Circulating microRNAs (miRs) have recently been associated with processes in CHD development, and may therefore represent new potential risk markers. The aim of the study was to assess the incremental value of adding circulating miRs to the Framingham Risk Score (FRS). Methods: This is a case-control study with a 10-year observation period, with fatal and non-fatal myocardial infarction (MI) as endpoint. At baseline, ten candidate miRs were quantified by real-time polymerase chain reaction in serum samples from 195 healthy participants (60–79 years old). During the follow-up, 96 participants experienced either a fatal (n = 36) or a non-fatal MI (n = 60), whereas the controls (n = 99) remained healthy. By using best subset logistic regression, we identified the miRs that together with the FRS for hard CHD best predicted future MI. The model evaluation was performed by 10-fold cross-validation reporting area under curve (AUC) from the receiver operating characteristic curve (ROC). Results: The best miR-based logistic regression risk-prediction model for MI consisted of a combination of miR-21-5p, miR-26a-5p, mir-29c-3p, miR-144-3p and miR-151a-5p. By adding these 5 miRs to the FRS, AUC increased from 0.66 to 0.80. In comparison, adding other important CHD risk factors (waist-hip ratio, triglycerides, glucose, creatinine) to the FRS only increased AUC from 0.66 to 0.68. Conclusions: Circulating levels of miRs can add value on top of traditional risk markers in predicting future MI in healthy individuals. Graphical abstract: Image 1 Highlights: 6 circulating microRNAs were associated with 10-year risk of myocardial infarction. Adding 5 microRNAs to the Framingham Risk Score significantly improved prediction. Adding other risk factors to the Framingham Risk Score did not improve prediction.